A safe and inexpensive technique of retrieval of gallbladder specimen after laparoscopy - I. Memon, A.; A. Ali, S.; G. Soomro, A.; J. Siddique, A. (Scientific Journal of Medical Science, 2013)
Laparoscopic cholecystectomy is associated with greater chances of intra abdominal stone spillage and implantation and port site contamination when gallbladder specimen is retrieved without endobag. Economical sterile surgical gloves can be used instead of expensive commercial endobags to retrieve the gallbladder specimen and also intra abdominal spilled stones safely without complications. Evaluate the safety and cost effectiveness of sterile surgical glove endobag technique for retrieval of gallbladder specimen after laparoscopic cholecystectomy. Four hundred patients with the diagnosis of symptomatic uncomplicated cholelithiasis, who underwent laparoscopic cholecystectomy with four port technique, were included in the study. In all these patients sterile surgical hand glove endobag (size 6½, 7) was inserted through 10mm umbilical port and gall bladder specimen was retrieved along with any spilled gallstone. Tense and distended gallbladders with packed stones were decompressed prior to retrieval without enlargement of the facial opening. The whole procedure was done under direct vision. Patients less than 15 years age, known cirrhotic and carcinoma gallbladder were excluded from this study. The whole process is observed for its safety and cost effectiveness. Gall bladder specimen in all four hundred cases, (276 (69%) female and 124 (31%) were male) retrieved through the 10mm umbilical port in surgical glove endobag. In 36 (9%) cases gallbladder was acutely inflamed and oedematous, which were opened and decompressed at the umbilical port site inside the endobag before retrieval. In 20 (5%) patients wound infection observed at the umbilical port site. In 01 (0.25%) patient spilled gall stones were recovered after two years from supra umbilical port presented as a chronic discharging sinus. Surgical glove endobag technique is simple, safe and economical with fewer complications.